(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
New NaLi\(_2\)PO\(_4\), phosphor doped with 0.5 mole% Eu\(^3\)\(^+\) prepared by solid state method were used for carbon dosimetry. XRD of the material matched with the data available in the literature (JCPDS file #80-2110) and confirmed formation of the material in its orthorhombic structure. The TL of the carbon beam irradiated sample recorded on Harshaw TLD-3500 reader. The samples are irradiated for different fluencies from the range of \(5× 10^9\) to \(1× 10^13\) ions cm\(^-2\). TL glow curve consist of single main TL peak around 457 K surrounded by kinks at 408, 504 and 542 K. TL glow curve of the carbon irradiated sample has same shape as that of gamma irradiated one. With increasing dose the intensity is increases. The phosphor is much more sensitive than the standard available standard phosphor. It is about 6.5 and 41.3 times more sensitive than the TLD-100 and TLD-700H. For these range of fluences phosphor show sub-linearity. Efficiency of the for phosphor for C\(^6+\) with respect to gamma radiation is calculated and is around 0.50754 for the fluence of \(5× 10^09\) ions cm\(^-2 \).